FINANCIAL TECHNOLOGY TREND: THE ANALYSIS OF FORWARDNESS SOCIETY IMPLEMENTING OF FINANCIAL TECHNOLOGY AT KEDIRI, 2020 - Atik Tri Andari; Elmi Rakhma Aalin; Eti Putranti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to examine the forwardness of society at Kediri implementing financial technology. This study used risk, financial technology facilities, and public interest as independent variables that affect community readiness. We did a survey to collect questionnaire data from 400 respondents. The results of this study provide empirical evidence that society at Kediri have been able to adapt financial technology. The risk factor for transaction errors can also be minimized by using financial technology, so society have tendency to implement financial technology